Research group librarian – a cooperating partner in research? - Olsen, Heidi Kristin (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
Academic libraries encounter many challenges when providing services for researchers and it is evident that use of the library in information searches has reduced significantly over time and continues to decrease. However, a study in Norway in 2007, at Vestfold University College (VUC), demonstrated that there is great potential to increase faculty staff’s use of the library’s digital resources with the right form of engagement. The findings led VUC’s library to focus on its services for this particular user group. In 2009, VUC library initiated a study to investigate the possible effects of a librarian participating as a ‘Research Group Librarian’. The research project, in which this new role was tried out, was called ‘Kindergarten space, materiality, learning and meaning-making’. This was a three year project, funded by the Research Council of Norway. There were eight part time researchers involved in this project, two senior researchers and the research group librarian. The study adopted an ethnographic approach. The research group librarian was a fully participating member of the research team throughout the project. The empirical sources for the study included: • semi-structured interviews with the project leader and the participating researchers: short individual interviews at the beginning of the project with each of the research group participants; several group interviews with the majority of the research team midway in the project; • observation and field notes The results are presented under the following categories: • implications for the researcher; emphasising behaviour in relation to information search and reference management skills; • communication and information within, and evolving from, the project; • collaboration in writing a review article; • implications for the library – internal, and at VUC in general; • the librarian’s role – a ‘boundary worker’? The study demonstrated that as a member of a research group a librarian can have positive impact on the researchers’ work. Appropriate library services become more distinct. Ideas for new library services for the user group evolve and develop naturally during the engagement process. Although this is a minor study and insufficient to make generalisations, the findings are interesting and worth considering in the further development of academic library services for faculty staff and researchers.